Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 (JOURNAL OF BIOGEOGRAPHY, 1995)
A marginal improvement in the response of Quercus ilex adult trees to drought appears to occur under a long-term natural CO2 enrichment. This is expressed, for example, by the absence of midday stomatal closure in trees growing under elevated CO2. Some protection against high irradiance and high temperature seems also to occur at the photochemical level, presumably as a result of more carbon available to the consumption of excess light energy. This would allow a better performance of the plants grown under elevated CO2 during the warmer hours of the day and therefore playing an important adaptation role under drought conditions. A marginal increase in the concentration of soluble sugars and starch was observed in the leaves of trees growing at elevated CO2 as compared with plants at ambient CO2, mainly during the midday hours. We may speculate that this will be advantageous both in terms of carbohydrate reserves for growth (e.g. more roots) and osmotic adjustment.
From Duplicate 2 (Leaf metabolism during summer drought in Quercus ilex trees with lifetime exposure to elevated CO2 - Chaves, M M; Pereira, J S; Cerasoli, S; CliftonBrown, J; Miglietta, F; Raschi, A)